Comportamento de cocriação de valor do consumidor : moderação e consequências - Frio, Ricardo Saraiva (2014)
The debate concerning value co-creation began to arouse the interest of Marketing scholars after the proposition of service-dominant logic. There is a large range of publications on the subject, although few of them represent empirical work. According to available literature, we see the need to identify backgrounds and consequences of that behavior. Starting from the proposal of Yi and Gong (2013), the customer value co-creation behavior is analyzed as a third-order construct, consisting of eight first-order constructs: information seeking, information sharing, responsible behavior and personal interaction associated with participation, advocacy, feedback, help and tolerance, corresponding to citizen behavior. Thus the aim of this work was to analyze the customer value co-creation behavior as an antecedent of satisfaction and loyalty. Also, we sought to evaluate the relationship time as a moderator from second- and third-order constructs. Two data collections were carried out. At first the customer value co-creation behavior scale was validated from a sample of 515 students. The results pointed out to the need to exclude five variables, but the eight first-order constructs structure was maintained and the hierarchical relation was confirmed. The aim of the second study was to test from a sample of 175 consumers the hypothesis that the customer value co-creation behavior precedes satisfaction and loyalty, and the results confirm this assumption. The relationship time worked as a moderator between citizen behavior and value co-creation, however, this relationship was not identified in participation. Future studies should provide new consequences and antecedents of this behavior.